Collaborative Practicum with Experimental Demonstration for Teaching the Concept of Production of Bioplastic to Vocational Students to Support the Sustainability Development Goals - Dani Nandiyanto, Asep Bayu; Fiandini, Meli; Hofifah, Siti Nur; Ragadhita, Risti; Al Husaeni, Dwi Fitria; Al Husaeni, Dwi Novia; Maryanti, Rina; Masek, Alias (Journal of Technical Education and Training, 2022)
The purpose of this study was to investigate collaborative practicum using experimental demonstrations for teaching the concept of making bioplastics to vocational students. This research was conducted using a one group pretest-posttest design which was carried out through collaborative practicum to 15 students vocational at Bandung, Indonesia. The teaching process was carried out using demonstration videos (as learning media). The manufacture of bioplastics is done by dissolving starch, glycerol, and vinegar using water which is then cooked at a temperature of 60°C so that gelatinization occurs. The resulting bioplastic has good biodegradability property, which can be degraded in 2-week immersion and overgrown with fungi as confirmed by the identical FTIR patterns. The results show that students understand the concept that is indicated by increasing the pretest and posttest scores. The increase in the gain of pretest and posttest scores varied between 13.33-53.33. The statistical analysis indicate that the students' post-test scores increased significantly. The experimental demonstrations using available materials makes students more interactive because students want to try it themselves. This study is expected to have an impact on the further teaching of experimental demonstration research which is believed to provide good learning success for students.